Adverse respiratory outcomes following conventional long‐course radiotherapy for non‐small‐cell lung cancer in patients with pre‐existing pulmonary fibrosis: A comparative retrospective study. Issue 4 (9th May 2020) - Bajraszewski, Clare; Manser, Renee; Chu, James; Cox, R Ashley; Tran, Phillip; Duffy, Mary; Irving, Louis; Herschtal, Alan; Siva, Shankar; Ball, David
Abstract: Introduction: There is some evidence to suggest that patients with underlying pulmonary fibrosis (PF) have increased risk of adverse respiratory and survival outcomes, when treated with conventional, long‐course radiotherapy (RT) for non‐small‐cell lung cancer (NSCLC). We performed a retrospective analysis to determine the size of these risks. Methods: Data from 21 patients with PF (cases) were retrospectively analysed for respiratory toxicity and mortality outcomes, and compared with 84 patients without PF (non‐cases). Age and mean lung dose were included as covariates in regression analyses. The additional predictive value of other patient, disease and treatment characteristics on radiation pneumonitis (RP) risk and severity was explored. Results: There was a numerical (though not statistically significant) increase in grade ≥ 2 RP among PF cases (OR 2.74, P = 0.074). Cases were significantly more likely to discontinue radical treatment early (OR 6.10, P = 0.015). There was a significant association between increased RP severity and underlying PF ( P = 0.039), with RP strongly implicated in the death in 3 of 21 cases (14.3%) compared to 1 non‐case (1.2%). Cases experienced increased grade ≥ 2 respiratory toxicity otherwise (OR 4.35, P = 0.020) and poorer median overall survival (0.6 versus 1.7 years, P < 0.001). Two cases, and no non‐cases, died during the proposed RT period. None of the analysed patient, disease or treatment factors, was a significant additional predictor of RP risk/severity. Conclusion: Patients with PF are at increased risk of treatment discontinuation, respiratory morbidity and mortality, and poor survival following conventional RT for NSCLC. Caution should be exercised when offering high‐dose RT to these patients.